Squash and a Squeeze - Donaldson, Julia; Scheffler, Axel (ill.) (London Macmillan, 2015)
A bit of a classic... A goat on the bed and a cow on the table tapping out of a jig.
Contains colourful pictures
Keywords: Children-Story